Dissolved Mn(III) is a key redox intermediate in sediments of a seasonally euxinic coastal basin - R. Klomp; R. Klomp; O. M. Żygadłowska; M. S. M. Jetten; V. E. Oldham; N. A. G. M. van Helmond; N. A. G. M. van Helmond; C. P. Slomp; C. P. Slomp; W. K. Lenstra; W. K. Lenstra (Biogeosciences)
Manganese (Mn) is an essential micronutrient and key redox intermediate in marine systems. The role of organically complexed dissolved Mn(III) (dMn(III)-L) as an electron acceptor and donor in marine environments is still incompletely understood. Here, we use geochemical depth profiles of solutes and solids for the sediment and overlying waters and a reactive transport model to reconstruct the seasonality in sedimentary dMn(III)-L dynamics and benthic Mn release in a eutrophic, seasonally euxinic coastal basin (Lake Grevelingen, the Netherlands). Our model results suggest that dMn(III)-L is a major component of the dissolved Mn pool throughout the year. According to the model, there are three major sources of pore water dMn(III)-L when oxygen (O2) is present in the bottom water, namely reduction of Mn oxides coupled to the oxidation of Fe(II), reduction of Mn oxides coupled to organic matter degradation, and oxidation of Mn(II) with O2. Removal of pore water dMn(III)-L is inferred to primarily take place through reduction by dissolved Fe(II). When bottom waters are euxinic in summer, model-calculated rates of sedimentary Mn cycling decrease strongly because of a lower supply of Mn oxides. The dMn(III)-L transformations in summer mostly involve reactions with Fe(II) and organic matter. Modeled benthic release of Mn mainly occurs as dMn(III)-L when bottom waters are oxic, as Mn(II) upon initial bottom-water euxinia and as both Mn(II) and dMn(III)-L when the euxinia becomes persistent. Our model findings highlight strong interactions between the sedimentary Fe and Mn cycles. Dissolved Mn(III)-L is a relatively stable and mobile Mn species, compared to Mn(II), and is therefore more easily transported laterally throughout the coastal zone and possibly also to open marine waters.